Nurses' perceptions of the vulnerabilities to STD/AIDS in light of the process of adolescence - Ítalo Rodolfo Silva; Antonio Marcos Tosoli Gomes; Glaucia Valente Valadares; Nereida Lúcia Palko dos Santos; Thiago Privado da Silva; Joséte Luzia Leite
Objective: to understand the perception of nurses on the vulnerabilities to STD/AIDS in light of the process of adolescence.Method: qualitative research conducted with 15 nurses in a centre for the studies of adolescent healthcare of a university hospital in Rio de Janeiro/Brazil. The adopted theoretical and methodological frameworks were the Complexity Theory and the Grounded Theory, respectively. The semi-structured interview was used to collect data from January to August 2012.Results: this research presents the category: Nurses' perceptions of the vulnerabilities to STD/AIDS in light of the process of adolescence, and the subcategories: Risks and uncertainties of the process of adolescence: paths to STD/AIDS; Age-adolescence complex: expanding knowledge from the perception of nurses.Conclusion: once the nurses understand the complexity of adolescence, they create strategies to reduce the vulnerability of adolescents to STD/AIDS. This signals the need to invest in education, assistance and the management of nursing care for adolescents.